Complete Set of Diketopyrrolopyrrole Centrosymmetrical Cofacial Stacked Pairs. Issue 21 (28th July 2022) - Luňák, Stanislav; Weiter, Martin; Vala, Martin
Abstract: Stacked centrosymmetrical dimers and simultaneously H‐bonded and stacked hexamers of thiophene‐substituted diketopyrrolopyrrole (ThDPP) were studied using DFT as models for crystals with slipped‐stacked molecules in 1D columns. Eight stacked dimer arrangements were found, six of which are driven by the minimisation of electron repulsion and realised by placing the partially negatively charged atoms of the diketopyrrolopyrrole rings below the centre of an adjacent thiophene ring. Four of these stacks are related to N, N' ‐dialkylated derivatives of ThDPP found in the literature, while a further one is related to an N, N' ‐diacylated derivative. An analogous set of eight stacks was discovered computationally for phenyl‐substituted DPP (PhDPP), four of which are known among H‐bonded DPP pigments, and one more among N, N' ‐dialkylated PhDPP derivatives. The results shed more light on the mechanisms that drive the formation of stacks between nonaromatic (DPP) and aromatic (Th, Ph) rings. The excitation energies of the lowest four singlet states computed by TD DFT enabled excitonic coupling and energy separation between Frenkel‐resonance‐type and charge‐transfer states to be established, depending on the equilibrium stack geometry. Abstract : Stacking geometry driven by electron repulsion : Eight centrosymmetrical stacks of cofacial diketopyrrolopyrrole dimers were located by DFT modelling, six of which were characterised by placing one of the partially negatively charged C, N, and O atoms of the nonaromatic DPP rings near the centre of the aromatic thiophene ring of the adjacent molecule. The binding energy of the most stable configuration was calculated to be 16.6 kcal/mol.